Honouring a Nation A History of Australia's Honours System - Fox, Karen (ANU Press, 2022)
The first detailed history of imperial and national honours in Australia, Honouring a Nation tells the story of the honours system's transformation from instrument of imperial unity to national institution. From the extension of British honours to colonial Australasia in the nineteenth century, through to Tony Abbott's revival of knighthoods in the twenty-first, this book explains how the system has worked, traces the arguments of its supporters and critics, and looks both at those who received awards and those who declined them. Honouring a Nation brings to life a long history of debate over honours, including wrangles over State rights, gender imbalances in honours lists, and the emergence and hardening of the Labor/Liberal divide over British awards, illuminating issues that are still part of Australian life-and of the honours system-today. The history of the honours system is equally the history of the nation, revealing who Australians were, what they have become, what they value, and the things that have unified and divided them.